Application viability evaluation of the Minimum Quantity Lubrication coolant technique under different flow rates in Plunge Cylindrical Grinding of the ABNT 4340 steel with aluminum oxide wheel - Rodriguez,Rafael Lemes (2017)
Abstract The coolant delivery technique known as Minimal Quantity Lubrication (MQL) has been employed in machining since the end of the 20th Century and has gained considerable evidence in the last years as a viable alternative to the use of the conventional coolant technique (flood). Due to the low oil flow rate delivered by the MQL technique in grinding operations, that generally varies from 20 to 240 ml / h in relation to near 600,000 ml / h flow rate of the conventional coolant technique, the MQL technique provides a reduced risk for human health and environmental damage associated with the use, maintenance and disposal of cutting fluids. In this context, this study was carried out to evaluate the application viability of the minimum quantity lubrication coolant technique under different flow rates in the plunge cylindrical grinding of ABNT 4340 steel with an aluminum oxide wheel. Three flow rates were tested: 30, 60 and 120 ml/h. Grinding trials with the conventional coolant delivery method were also tested for comparative purposes. The output variables used to assess the efficiency of the MQL technique in this work are: roughness, roundness and hardness of the workpiece. Grinding wheel wear and power consumption were also monitored. The results showed that, despite the higher values of roughness and roundness of the workpiece, as well as the grinding wheel wear, the values of these same parameters obtained after machining with the MQL technique were close to those obtained after machining with the conventional technique. No thermal damages and cracks on the machined surface, or even below the machined surface, were observed after grinding ABNT 4340 steel irrespective of the coolant-lubrication condition investigated. The results showed that the MQL with 120 ml/h can be an alternative coolant technique due to cleaner environment and lower consumption of fluid in grinding under the conditions investigated in this work.